The emerging role of AI technologies in supporting digital diplomacy and shaping international relations (The International Journal for Scientific Research, 2025)
Artificial Intelligence (AI) is increasingly influencing global diplomacy and international relations by transforming how states engage, negotiate, and communicate in the digital age. This study explores the integration of AI technologies—such as machine learning, natural language processing, and big data analytics—into diplomatic processes, highlighting their role in enhancing decision-making, crisis management, and global cooperation. AI-driven tools facilitate real-time data analysis, sentiment tracking, and predictive analytics, enabling diplomats to assess geopolitical trends and respond proactively to emerging challenges. Additionally, AI supports digital diplomacy by automating translation, optimizing diplomatic communications, and countering misinformation. While AI presents significant opportunities, challenges related to ethical considerations, bias, cybersecurity, and the potential erosion of human agency in decision-making remain. This paper examines case studies of AI applications in diplomacy, evaluates their implications for global governance, and proposes strategies to balance technological innovation with ethical and strategic concerns. The findings underscore AI’s growing impact on international relations and the necessity for adaptive governance frameworks to harness its potential responsibly.
Keywords: Artificial Intelligence (AI); Digital Diplomacy; International Relations